The application of self-assembled nanostructures in peptide-based subunit vaccine development. (August 2017) - Zhao, Guangzu; Chandrudu, Saranya; Skwarczynski, Mariusz; Toth, Istvan
Graphical abstract: Highlights: Smaller polymer-peptide conjugates-based nanoparticles are often more immunogenic. Lipid-antigen conjugates-based nanoparticles can interact with immune receptors. Peptides with β-sheet conformation usually form nanofibers. α-Helical and random coil peptides tend to self-assemble into nanoparticles. Peptide-based nanostructures are usually poorer inducers of immune responses. Abstract: Peptide based-vaccines are becoming one of the most widely investigated prophylactic and therapeutic health care interventions against a variety of diseases, including cancer. However, the lack of a safe and highly efficient adjuvant (immune stimulant) is regarded as the biggest obstacle to vaccine development. The incorporation of a peptide antigen in a nanostructure-based delivery system was recently shown to overcome this obstacle. Nanostructures are often formed from antigens conjugated to molecules such as polymers, lipids, and peptide, with the help of self-assembly phenomenon. This review describes the application of self-assembly process for the production of peptide-based vaccine candidates and the ability of these nanostructures to stimulate humoral and cellular immune responses.